2022
DOI: 10.3389/fnagi.2022.921518
|View full text |Cite
|
Sign up to set email alerts
|

Verbal intelligence and leisure activities are associated with cognitive performance and resting-state electroencephalogram

Abstract: Cognitive reserve (CR) is the adaptability of cognitive processes that helps to explain differences in the susceptibility of cognitive or daily functions to resist the onslaught of brain-related injury or the normal aging process. The underlying brain mechanisms of CR studied through electroencephalogram (EEG) are scarcely reported. To our knowledge, few studies have considered a combination of exclusively dynamic proxy measures of CR. We evaluated the association of CR with cognition and resting-state EEG in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The study found that dynamic proxy measures of CR are positively associated with alpha power in resting‐state EEG and leisure activities are a significant positive predictor of alpha 2 rhythms. However, physical activities were not found to be predictors of cognitive performance or resting‐state EEG 65 …”
Section: Physiological Brain Aging and Crmentioning
confidence: 87%
See 2 more Smart Citations
“…The study found that dynamic proxy measures of CR are positively associated with alpha power in resting‐state EEG and leisure activities are a significant positive predictor of alpha 2 rhythms. However, physical activities were not found to be predictors of cognitive performance or resting‐state EEG 65 …”
Section: Physiological Brain Aging and Crmentioning
confidence: 87%
“…However, physical activities were not found to be predictors of cognitive performance or resting-state EEG. 65 The results by Buján et al showed moderate negative correlations between the CRIq and occipital current source density in delta and beta 2 frequency bands, as well as positive associations between the CRIq and inter-and intrahemispheric lagged-linear connectivity measures. 66 The effect of age on cognitive performance was stronger for higher values of both measures, suggesting that lower values might protect or compensate for the effects of age on cognition.…”
Section: Electromagnetic Brain Activity and Crmentioning
confidence: 93%
See 1 more Smart Citation
“…More research is needed to elucidate the role of cognitive deficits such as verbal comprehension, working memory, and processing speed in learning disorders. To further clarify the relative role of such cognitive domains as some of the main contributors to the symptomatology of LDs, we propose that a more thorough relationship should be traced between indices of cognitive performance and the activity of different networks of the EEG resting state because several studies have proposed that resting-state measures are useful predictors of cognitive performance in different kinds of samples, from children [64] to healthy adults [65] and elderly individuals [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, more and more attention has been paid to the role of leisure activities as a protective factor against cognitive function in the older people. A recent study shows that participating in leisure activities, not only as a prevention strategy, but even as an intervention in later life, may promote better cognitive performance through compensation or neural efficiency mechanisms [ 14 ]. The potential mechanism for the protective effect of leisure activities on cognitive function is still unclear.…”
Section: Introductionmentioning
confidence: 99%